PERAN PEREMPUAN INDONESIA DALAM PERJUANGAN KEBANGSAAN (MEMBACA TOKOH NYAI ONTOSOROH PADA NOVEL BUMI MANUSIA - Muhamad Adji (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Women have often overlooked in the history of struggle of the Indonesian nation. In the history books of the nation, we aremore familiar with men heroic figures than women, so not many know how much women’s roles in the establishment of a nation calledIndonesia. Nyai Ontosoroh is a character in the novel Bumi Manusia, by Pramoedya Ananta Toer, who is recognized as the Indonesianliterary canon. It is the representation of women who were born and live in the nation before of independence of Indonesian nation. Althoughborn from the lowest class in the structure of Indonesian society and never earned the right to attend school, Nyai Ontosoroh have a largerole in the Indonesian struggle until the establishment of an independent Indonesian nation. The questions that guide the writing are 1) howbig Nyai Ontosoroh role in the struggle of the Indonesian nation and 2) what role do Nyai Ontosoroh in the struggle of the Indonesian nation.Conclusions obtained from studies that Nyai Ontosoroh is a representation of women in Indonesia who has a big role in realizing nationalindependence of Indonesia. That role not only in the form of concrete action, but the her conviction to have more faith in their own strengththan to rely on foreign strenght like the Dutch colonial government